(untitled) (Revista Venezolana de Salud Pública, 2020)
In order to determine cervical pathologies in women attending in the San Francisco type I urban ambulatory. It has been made a descriptive cross-sectional investigation, with a non-probabilistic, accidental, sample consisting of 100 women who underwent vaginal cytology whose analysis was through the Bethesda system. Using a questionnaire-type instrument with closed questions was used with which the gynecological-obstetric history was investigated. The data obtained were processed with the Excel program 2010 and later they were represented in tables through descriptive statistics such as absolute numbers and percentages. Of the total of processed samples, 77% were obtained with cervical pathologies, reporting 61.03% with reactive changes; 46.75% with inflammatory type alteration and 29.87% abnormal epithelial cells. When analyzing gynecological-obstetric history it can be seen that 61.03% are represented by age; 59.74% multiple gestations; 57.14% multiple sexual partners throughout their lives; 9.09% early sexarchy and 3.89% promiscuous. On the other hand, of the patients who present abnormal epithelial changes according to Bethesda, it is reported that 60.87% report low grade LIE; 30.43% present ASCUS and 8.70% high grade LIE. Finally, with this study, the aim was to recognize and provide accurate information and statistical data to the San Francisco type I urban ambulatory, to promote prevention and avoid the progression of these pathologies, helping to reduce morbidity and mortality from this cause.